Island platforms and the hyper-terrestrialisation of Singapore's smart city-state - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2024)
This paper foregrounds the importance of underlying territorial formations in realising a vision of the smart city. It argues that as a political technology of the state, territory should be understood as a platform upon which data works and the smart city unfolds. In this view, island territories – of which bordered city-states like Singapore provide paradigmatic examples – provide an integral, yet hitherto unexplored, component in the realisation of urban “smartness”. We illustrate these theoretical arguments through an analysis of how the territorial constraints that characterise Singapore’s island platform enable the state to accurately and effectively realise its vision of a smart city. As both an island city and a city-state, Singapore’s territory is a political technology that is just as important in realising the state’s vision of smartness as the adoption of digital technologies and the management of data. Drawing on 27 interviews with 31 architects of Singapore’s Smart Nation, we empirically explore the integration of data, city and territory through the platform; the “hardness” of data and the “softness” of the city; and the hyper-terrestrialisation of “smartness” in Singapore. Overall, we demonstrate how the idea of territory as a platform provides a generative counterpoint to critiques of platform urbanism.